Dependent and Independent Cognitive Style Learning Model in Mathematics Subject Outcomes - Abdul Aziz Batubara (Randwick International of Education and Linguistics Science Journal, 2023)
The need to improve learning outcomes in class VII students of Al Washliyah Middle School, then a learning model is sought that encourages students to like mathematics, motivate students to learn independently, and encourage students to have curiosity, and involve active students in learning, both mentally mentally , physical, or social. Therefore a teacher must be able to understand the cognitive style of students. This is because the ability of people in processing information of each individual is different. Therefore this study tests and compares several learning models that are more effective in the learning outcomes of the Alwashliyah Middle School Mathematics, Deli Serdang among them is 1) Problem Learning Model Posing with direct learning models, 2) Independent Field Cognitive Style with Field Dependent Cognitive Style. This study also analyzed whether there was an interaction in the learning model and cognitive style of students that could influence the learning outcomes of the Mathematics of Class VII of Al Washliyah Middle School. The method used in this study is a pseudo experimental method with a factory research design of 2 x 2. This study was conducted at Al Washliyah Middle School, Deli Serdang. The results of this study among others are 1) Mathematical learning outcomes of students taught with a higher problem posing model than direct learning models, 2) Students who have cognitive styles of independent fields obtain higher mathematical learning outcomes than mathematical learning outcomes students who have cognitive styles Field Dependent.